2014
DOI: 10.1093/hmg/ddu474
|View full text |Cite
|
Sign up to set email alerts
|

ILDR1 null mice, a model of human deafness DFNB42, show structural aberrations of tricellular tight junctions and degeneration of auditory hair cells

Abstract: In the mammalian inner ear, bicellular and tricellular tight junctions (tTJs) seal the paracellular space between epithelial cells. Tricellulin and immunoglobulin-like (Ig-like) domain containing receptor 1 (ILDR1, also referred to as angulin-2) localize to tTJs of the sensory and non-sensory epithelia in the organ of Corti and vestibular end organs. Recessive mutations of TRIC (DFNB49) encoding tricellulin and ILDR1 (DFNB42) cause human nonsyndromic deafness. However, the pathophysiology of DFNB42 deafness re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 58 publications
1
51
0
Order By: Relevance
“…This fits with no other aspect of our findings, and seems to reflect cellular processes not assessed by acute examination. Notably, several published genetic impairments of tight junctions apparently do not promote EP reduction (Bahloul et al, 2009; Ben-Yosef et al, 2003; Kitajiri et al, 2014; Morozko et al, 2014; Nakano et al, 2009; Nayak et al, 2013). Young B6 mice exposed to supercritical noise levels may re-form tight junctions that are severely dysfunctional, leading to greater paracellular ion leakage and permanent EP collapse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fits with no other aspect of our findings, and seems to reflect cellular processes not assessed by acute examination. Notably, several published genetic impairments of tight junctions apparently do not promote EP reduction (Bahloul et al, 2009; Ben-Yosef et al, 2003; Kitajiri et al, 2014; Morozko et al, 2014; Nakano et al, 2009; Nayak et al, 2013). Young B6 mice exposed to supercritical noise levels may re-form tight junctions that are severely dysfunctional, leading to greater paracellular ion leakage and permanent EP collapse.…”
Section: Discussionmentioning
confidence: 99%
“…Both tears and holes would promote mixing of endolymph and perilymph, ostensibly exposing hair cells to toxically high K + levels, thereby magnifying hair cell and hearing loss. Such a process is supported by knockout models for tight junctional proteins such as vezatin, claudin-9, claudin-14, occludin, angulin-2 (Ildr1), and tricellulin (Bahloul et al, 2009; Ben-Yosef et al, 2003; Kitajiri et al, 2014; Morozko et al, 2014; Nakano et al, 2009; Nayak et al, 2013). Some of these models (claudin-9 and -14) show both reduced electrical resistance of tight junctions and hair cell loss, despite a normal EP.…”
Section: Introductionmentioning
confidence: 97%
“…Such leakage is normally minimized by tight junctions that line cell-cell junctions of the reticular lamina. Elimination of tight junction proteins vezatin, claudin-9, claudin-14, occludin, angulin-2 (Ildr1), or tricellulin promotes hearing loss in mice (Ben-Yosef et al 2003;Bahloul et al 2009;Nakano et al 2009;Nayak et al 2013;Kitajiri et al 2014;Morozko et al 2014). In the case of claudins-9 and -14, in vitro recordings have shown that the junctions become leaky, likely allowing K + to enter the organ of Corti and potentially killing hair cells through K + toxicity.…”
Section: Genes and Processes That Establish Or Modulate The Epmentioning
confidence: 99%
“…In the inner ear, epithelial cells delimit the fluid-filled compartments and the tight junctions between adjacent cells prevent intermixing of the extracellular fluids (Gulley and Reese 1976; Jahnke 1975). Several tight junction proteins are found in the inner ear epithelia and variants in many of these have been associated with hearing loss in humans and mouse mutants (Ben-Yosef et al 2003; Borck et al 2011; Citi et al 1988; Gow et al 2004; Higashi et al 2013; Kitajiri et al 2004a; Kitajiri et al 2004b; Lee et al 2012; Morozko et al 2014; Nakano et al 2009; Nayak et al 2013; Raphael and Altschuler 1991; Riazuddin et al 2006; Wilcox et al 2001). …”
Section: Introductionmentioning
confidence: 99%